Lenguajes documentales y administración pública: análisis de tesauros en lengua española - Peón Pérez, Jaime Luis (Revista General de Información y Documentación, 2005)
Trhis item describes six thesauri about Public Administration in Spanish language, Thesauri.From the evidence of the utility of documentary languages like technical skills used for the analysis of the contents of the documents in Public Administration documentary units and services.
Keywords: Documentary languages; Documentation services; Public Administration; Spanish language; Thesauri